Probiotics, Prebiotics, Synbiotics and Dental Caries. New Perspectives, Suggestions, and Patient Coaching Approach for a Cavity-Free Mouth - Markos Amargianitakis; Maria Antoniadou; Christos Rahiotis; Theodoros Varzakas (Applied Sciences, 2021)
Probiotic therapy forms a new strategy for dental caries prevention. Probiotic microorganisms possess the ability to displace cariogenic microorganisms and colonize the oral cavity. They can produce various antimicrobial substances such as bacteriocins, bacteriocin-like peptides, lactic acid, and hydrogen peroxide. Dairy products may be ideal for probiotic administration in dental patients. Many other means have been proposed, primarily for those allergic to dairy components, such as capsules, liquid form, tablets, drops, lozenges, sweetened cakes, and ice creams. The last two forms can be used in a coaching approach for children and elderly patients who find it difficult to avoid sugary beverages in their daily routine and benefit from the suggestion of easy, cheap, and common forms of delicacies. In caries prevention, the concept of the effector strain is already considered an integral part of the contemporary caries cure or prevention strategy in adults. Adults, though, seem not to be favored as much as children at early ages by using probiotics primarily due to their oral microbiome’s stability. In this non-systematic review we describe the modes of action of probiotics, their use in the cariology field, their clinical potential, and propose options to prevent caries through a patient coaching approach for the daily dental practice.